Digital Explanations : Learning and Communicating Science with Student-created Digital Media : Final Report. - Hoban, Garry (Office for Learning and Teaching, 2016)
Final report of a Teaching Fellowship at the University of Wollongong. The Fellowship sought to support science academics and science teacher educators in implementing assignments that use a range of student-created digital media (for example, podcasts, digital story, slowmation, videos, and blended media which is a combination) to engage students in learning, explaining and communicating science.